Protesting Human Life Amendment; Supporting Women's Right to Choice by State Building on Mariposa Mall - Watkins, Howard::::::::: (1981)
Protesters walking in large circle holding signs: "When Does Life Begin For Women" "Coalition of Labor Union Women Support Choice!" Cindy Calvert with "A Woman's Life is a Human Life"